ZnO@ZnWO4 composite material, and preparation method and application thereof

CN118326368BActive Publication Date: 2026-10-27BEIJING INFORMATION SCI & TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410354835.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2026-10-27
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

然而单组分的MOS材料难以将气敏材料的灵敏度、选择性等性能优化到最佳,因此,通过组分设计以及协同效应开发复合氧化物材料,成为现在研究热点之一

Benefits of technology

本申请提供一种金属氧化物半导体复合材料,采用溶液蒸发诱导自组装法制备了WO3纳米材料,进一步通过CVD的方法原位复合了ZnO@ZnWO4敏感材料。通过控制沉积时间调控ZnO@ZnWO4材料的形貌和结构,同时利用二者的协同效应,实现对痕量H2S的检测,达到提高传感性能的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326368B_ABST
    Figure CN118326368B_ABST
Patent Text Reader

Abstract

The application discloses a ZnO@ZnWO4 composite material and a preparation method and application thereof, and the ZnO@ZnWO4 composite material is prepared through the following steps: WO3 nanomaterial is prepared through a solution evaporation induced self-assembly method; and the WO3 nanomaterial is in-situ compounded with ZnCl2 through a chemical vapor deposition method to generate the ZnO@ZnWO4 composite material. The sensitive material structure is regulated by controlling the deposition time, so that the H2S gas sensitive performance is significantly improved, and the trace H2S detection is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of gas-sensitive materials technology, specifically to a ZnO@ZnWO4 composite material, its preparation method, and its application. Background Technology

[0002] Currently, standardized gas detection methods typically require complex experimental procedures and expensive, cumbersome equipment, and do not provide real-time results. High-performance liquid chromatography (HPLC), gas chromatography (GC), and ion chromatography (IGC) offer high sensitivity for low concentrations of toxic gases and vapors. However, their drawbacks include complex sample preparation, high cost, and long detection times.

[0003] Since traditional air quality monitoring methods are no longer suitable for air quality monitoring, there is an urgent need to develop air quality monitoring instruments that are inexpensive, have a rapid response, operate at low temperatures, exhibit high selectivity, good stability, and good repeatability for detecting different toxic gases.

[0004] In recent years, researchers have studied various gas sensors, including metal oxide gas sensors, solid electrolyte gas sensors, electrochemical gas sensors, graphene-based gas sensors, and carbon material gas sensors.

[0005] Among numerous gas-sensitive materials, metal-oxide-semiconductor (MOS) materials, with their excellent physicochemical properties and unique structure, exhibit superior performance compared to other sensing materials, possessing higher sensitivity, faster response / recovery speed, and better stability, and have been extensively studied and developed in the field of gas sensors. However, single-component MOS materials are insufficient to optimize the sensitivity, selectivity, and other properties of gas-sensitive materials to their best potential. Therefore, developing composite oxide materials through component design and synergistic effects has become one of the current research hotspots.

[0006] Real-time and accurate monitoring of trace H2S gas is of great practical significance for environmental protection and human health. Summary of the Invention

[0007] To address the aforementioned deficiencies in this field, this application aims to provide a metal oxide semiconductor composite material, its preparation method, and its application.

[0008] According to one aspect of this application, a method for preparing a ZnO@ZnWO4 composite material is provided, comprising: WO3 nanomaterials were prepared by solution evaporation-induced self-assembly. ZnO@ZnWO4 composite material was generated by in-situ composite of WO3 nanomaterials and zinc salts via chemical vapor deposition. The zinc salts included ZnCl2.

[0009] According to some embodiments of this application, the calcination time for chemical vapor deposition is 2-8 hours.

[0010] According to some embodiments of this application, the calcination time for chemical vapor deposition is 2 hours.

[0011] According to some embodiments of this application, the mass ratio of WO3 nanomaterials to ZnCl2 is 1:3-1:8.

[0012] According to another aspect of this application, a ZnO@ZnWO4 composite material prepared by the above-described preparation method is provided, wherein the ZnO@ZnWO4 composite material forms an n-type heterojunction.

[0013] According to some embodiments of this application, the ZnO@ZnWO4 composite material has a flower-like structure.

[0014] According to some embodiments of this application, the flower-like structure includes: a flower-like structure composed of columnar aggregates and a flower-like structure composed of sheet-like aggregates; According to some embodiments of this application, it is a flower-like structure formed by sheet-like aggregates.

[0015] According to another aspect of this application, a gas sensor is also provided, which is made using the aforementioned composite material.

[0016] This application also provides an application of the above-mentioned gas sensor in H2S gas detection.

[0017] According to some embodiments of this application, the gas sensor has a sensitivity to H2S > 350.

[0018] According to some embodiments of this application, the lower limit for the gas sensor to detect H2S concentration is 0.05 ppm.

[0019] Compared with the prior art, this application has at least the following beneficial effects: This application provides a metal-oxide-semiconductor composite material. WO3 nanomaterials were prepared using a solution evaporation-induced self-assembly method, and ZnO@ZnWO4 sensing material was further composited in situ using CVD. By controlling the deposition time, the morphology and structure of the ZnO@ZnWO4 material were modulated. Simultaneously, the synergistic effect of the two materials was utilized to achieve the detection of trace H2S, thereby improving the sensing performance.

[0020] This application utilizes chemical vapor deposition (CVD) to in-situ composite ZnO@ZnWO4 materials, forming a sensitive material film on the surface of a flat electrode sheet. This film has advantages such as uniform particle size, high purity, and small particle size. Compared with traditional coating methods, CVD film formation is more uniform. Furthermore, by controlling process parameters, the morphology of the material can be adjusted using CVD film formation, thereby improving gas-sensing performance.

[0021] The improved gas-sensing performance of ZnO@ZnWO4-based sensors is mainly attributed to the modulation of their composition and morphology. Utilizing the "synergistic effect" of the components and the "interface effect" of the heterostructure, the sensor's recognition and conversion functions are enhanced, improving the selectivity and sensitivity of the gas sensor. The large specific surface area provides abundant active sites for the gas-sensing reaction. Simultaneously, the combination of a CVD uniform film formation method improves the utilization efficiency of the sensing element and enhances the gas-sensing performance. Attached Figure Description

[0022] Figure 1 SEM images of gas-sensitive materials used in exemplary embodiments and comparative examples of this application.

[0023] Figure 2 The image shows the XRD pattern of the gas-sensitive material in an example embodiment of this application.

[0024] Figure 3 The sensor prepared as an example embodiment and comparative example of this application shows its response sensitivity to 30 ppm H2S and 2 ppm NO2 at different operating temperatures.

[0025] Figure 4 The sensor prepared as an example embodiment and comparative example of this application shows the response sensitivity of the sensor to 50 ppm H2S at the optimal operating temperature.

[0026] Figure 5 The sensitivity-concentration gradient characteristic curve of the sensor prepared in Example 1 of this application for H2S gas at the optimal operating temperature.

[0027] Figure 6 The sensor prepared in Example 1 of this application exhibits selectivity for different gases at its optimal operating temperature of 200°C.

[0028] Figure 7 The stability test of the sensor prepared for Example 1 of this application against 30 ppm H2S at 200°C. Detailed Implementation

[0029] The technical solution of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0030] It should be particularly noted that similar substitutions and modifications made to this application are obvious to those skilled in the art, and they are all considered to be included in this application. Those skilled in the art can obviously make modifications or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit, and scope of this application to implement and apply the technology of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments.

[0031] Unless otherwise specified, this application is conducted under standard conditions or conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, whose manufacturers are not specified, are all conventional products that can be obtained commercially.

[0032] The following is a detailed description of this application.

[0033] As the applications of semiconductor metal-oxide gas sensors continue to expand into more sophisticated fields, the requirements for their gas-sensing performance are also constantly increasing, including lower detection limits, better selectivity, and higher sensitivity. Existing single MOS materials are insufficient to optimize the sensitivity and selectivity of gas-sensing materials to their best potential. The key to improving the performance of semiconductor metal-oxide gas sensors lies in modifying the sensitive material. This application designs a gas-sensing material with a high specific surface area by controlling the morphology of the sensitive material and combining it with the synergistic effect of heterostructures. This results in more active sites, and by combining two or more MOS materials to construct a heterojunction, complementary advantages are achieved, thereby improving the gas-sensing performance.

[0034] ZnO is a wide-bandgap (3.37 eV) semiconductor material that has been widely used as a gas-sensitive material for the detection of various gases. However, single-component ZnO still cannot meet the practical requirements of sensors. Therefore, this application introduces another bandgap-matched metal oxide heterojunction composite material, which can improve the gas-sensitive performance of MOS materials.

[0035] Ternary metal oxides have attracted much attention as new gas-sensitive materials. Compared with traditional metal oxides, they have many advantages such as high catalytic activity, chemical inertness, thermal stability, environmental friendliness and high gas sensitivity.

[0036] Based on this, this application prepared WO3 nanomaterials using a solution evaporation-induced self-assembly method. Furthermore, leveraging the low cost, high chemical stability, non-toxicity, high catalytic activity, magnetic properties, and luminescence properties of ZnWO4, ZnO@ZnWO4 sensing materials were in-situ composited using chemical vapor deposition (CVD). By controlling the deposition time to regulate the morphology and structure of the ZnO@ZnWO4 material, and utilizing the synergistic effect of the two materials, trace H2S detection was achieved, thereby improving the sensing performance.

[0037] The ZnO@ZnWO4 composite material forms heterojunctions, and by utilizing the synergistic effect of the two, the H2S gas-sensing performance is significantly improved, enabling the detection of trace H2S.

[0038] Gas Sensing Mechanism: For n-type semiconductors, when a ZnO@ZnWO4 gas sensor is placed in air, oxygen molecules will adsorb onto the surface of the ZnO@ZnWO4 material. These oxygen molecules are ionized by capturing free electrons from the conduction band of the ZnO@ZnWO4 composite material, resulting in negatively charged surface-adsorbed oxygen. The reaction is as follows: O 2(gas) → O 2(ads) O 2(ads) +e - →O 2- (ads) O 2- (ads) +e - →O - (ads) Therefore, a thick electron depletion layer forms on the surface of the composite material, creating a high potential barrier between adjacent ZnO and ZnWO4 grains, leading to an increase in the sensor's resistance. When the sensor comes into contact with the reducing gas H2S at a suitable operating temperature, H2S gas molecules adsorb onto the sensor surface and react with chemically adsorbed oxygen on the sensitive material surface. This releases trapped electrons into the conduction band of the sensitive material, reducing the width of the electron depletion layer. The increased electron concentration leads to an increase in the sensor's conductivity, manifested as a decrease in the resistance of the gas-sensitive element. The reaction between H2S and surface-adsorbed oxygen is as follows: H2S (gas) →H2S (ads) H2S (ads) +3 O - (ads) →SO2 + H2O + 3e - The technical solution of this application will be further described below with reference to specific embodiments.

[0039] Example 1 Synthesis of WO3 nanomaterials using a solvent evaporation-induced self-assembly method: 0.1 g of PEO-b-PS was dissolved in 5 mL of tetrahydrofuran (THF) to form a clear solution A; 0.4 g of WCl6 precursor solute was dissolved in 1 mL of ethanol and 0.42 mL of acetylacetone to form precursor solution B; solutions A and B were mixed and stirred to form a dark green solution; the mixed solvent was poured into a petri dish and evaporated at room temperature for 2 h, then transferred to an oven and evaporated at 100 °C for 24 h. After the organic solvent was completely evaporated, the spherical micelles were further assembled into an ordered mesoporous structure; the prepared organic-inorganic composite material was scraped out of the petri dish and heated at 350 °C in a vacuum atmosphere at a rate of 1 °C / min for 3 h, and then heated at 500 °C at a rate of 5 °C / min for 1 h. The copolymer phase underwent pyrolysis separation, and the PS segments of the block copolymer were transformed into amorphous carbon; the temperature was then heated to 450 °C in air at a rate of 5 °C / min and held for 2 h to completely remove the carbon residue in the mesopores, thus achieving the synthesis of mesoporous WO3 material.

[0040] CVD in-situ composite generation of ZnO@ZnWO4 composite material: Take 3.6 mg of WO3 material and mix it with deionized water in a mortar and grind it thoroughly into a slurry. Coat the slurry evenly on a flat electrode sheet. Take 10.8 mg of ZnCl2 precursor and place it in a quartz boat with a length of 5 cm and a height of 5 mm. Place the flat electrode sheet coated with WO3 upside down on top of the quartz boat and place it in the center of the heating area of ​​a tube furnace. Adjust the heating rate to 2℃ / min and the heating temperature to 400℃ and hold for 2 h. Allow it to cool naturally to room temperature to obtain the ZnO@ZnWO4 composite material, denoted as ZW1.

[0041] Sensor fabrication: The flat electrode sheet was cleaned sequentially with acetone and distilled water, and then treated with a plasma cleaner. WO3 material was coated onto the electrode sheet, which was then baked under an infrared lamp until dry. The electrode sheet was placed in a tube furnace, and ZnO@ZnWO4 material was generated in situ using CVD. The electrode sheet with the composite material was then welded onto a general-purpose side-heated hexagonal tube socket, thus obtaining a gas sensor made of ZW1 composite material.

[0042] Example 2 The preparation steps for WO3 nanomaterials are the same as in Example 1.

[0043] CVD in-situ composite generation of ZnO@ZnWO4 composite material: 3.6 mg of WO3 material was mixed with deionized water and placed in a mortar. The mixture was then ground into a slurry and evenly coated onto a flat electrode plate. 10.8 mg of ZnCl2 precursor was placed in a quartz boat that was 5 cm long and 5 mm high. The flat electrode plate coated with WO3 was placed upside down on top of the quartz boat and placed in the center of the heating zone of a tube furnace. The heating rate was adjusted to 2 °C / min and the heating temperature was 400 °C for 4 hours. The mixture was then allowed to cool naturally to room temperature to obtain the ZnO@ZnWO4 composite material, denoted as ZW2.

[0044] The sensor was fabricated in the same manner as in Example 1.

[0045] Example 3 The preparation steps for WO3 nanomaterials are the same as in Example 1.

[0046] CVD in-situ composite generation of ZnO@ZnWO4 composite material: Take 3.6 mg of WO3 material and mix it with deionized water in a mortar and grind it thoroughly into a slurry. Coat the slurry evenly on a flat electrode sheet. Take 10.8 mg of ZnCl2 precursor and place it in a quartz boat with a length of 5 cm and a height of 5 mm. Place the flat electrode sheet coated with WO3 upside down on top of the quartz boat and place it in the center of the heating area of ​​a tube furnace. Adjust the heating rate to 2℃ / min and the heating temperature to 400℃ and maintain it for 6 h. Allow it to cool naturally to room temperature to obtain the ZnO@ZnWO4 composite material, denoted as ZW3.

[0047] The sensor was fabricated in the same manner as in Example 1.

[0048] Example 4 The preparation steps for WO3 nanomaterials are the same as in Example 1.

[0049] CVD in-situ composite generation of ZnO@ZnWO4 composite material: Take 3.6 mg of WO3 material and mix it with deionized water in a mortar and grind it thoroughly into a slurry. Coat the slurry evenly on a flat electrode sheet. Take 10.8 mg of ZnCl2 precursor and place it in a quartz boat with a length of 5 cm and a height of 5 mm. Place the flat electrode sheet coated with WO3 upside down on top of the quartz boat and place it in the center of the heating area of ​​a tube furnace. Adjust the heating rate to 2℃ / min and the heating temperature to 400℃ and maintain it for 8 hours. Allow it to cool naturally to room temperature to obtain the ZnO@ZnWO4 composite material, denoted as ZW4.

[0050] The sensor was fabricated in the same manner as in Example 1.

[0051] Comparative Example 1 WO3 nanomaterials were prepared according to the method in Example 1.

[0052] Sensor fabrication: The flat electrode sheet was cleaned sequentially with acetone and distilled water, and then treated with a plasma cleaner. WO3 material was coated onto the electrode sheet, which was then baked under an infrared lamp until dry. The electrode sheet was placed in a ceramic boat and annealed at 200°C for 2 hours. The electrode sheet with WO3 material was then welded onto a general-purpose side-heated hexagonal tube socket, thus obtaining a gas sensor made of WO3 material.

[0053] Comparative Example 2 CVD in-situ composite generation of ZnO materials: 10.8 mg of ZnCl2 precursor was placed in a quartz boat that was 5 cm long and 5 mm high. The flat electrode was placed upside down on top of the quartz boat and placed in the center of the heating zone of the tube furnace. The heating rate was adjusted to 2 °C / min and the heating temperature was 400 °C for 2 hours. The material was then naturally cooled to room temperature to obtain ZnO material.

[0054] Sensor fabrication: The flat electrode sheet was cleaned sequentially with acetone and distilled water, and then treated with a plasma cleaner. The flat electrode sheet was placed in a tube furnace, and ZnO material was generated in situ using CVD. The flat electrode sheet with the sensitive material was then welded onto a general-purpose side-heated hexagonal tube socket, thus obtaining a gas sensor made of ZnO material.

[0055] Comparative Example 3 A 25% NH4OH solution was slowly added dropwise to a 0.06 mol / L Zn(CH3COO)2·2H2O solution, and the mixture was stirred vigorously until the pH reached 10.6. The mixture was then heated in an 80°C water bath for 2 hours to produce a Zn(OH)2 precipitate. The precipitate was collected by vacuum filtration and washed three times with deionized water and ethanol, respectively.

[0056] Preparation of tungstate (H2WO4) precursor: 15 g of ammonium tungstate was dissolved in 150 mL of deionized water and stirred vigorously. Then, 30 mL of nitric acid (3 mol / L) solution was slowly added to the solution, and stirring was continued at 80 °C for 1 h, resulting in precipitation. The precipitate was collected and washed several times with deionized water, etc. The washed precipitate was dried overnight at 80 °C to form the H2WO4 precursor.

[0057] The amount of precursor was determined, and the precursor was calcined at 750℃ for 2 hours to obtain ZnO / ZnWO4 powder.

[0058] Sensor fabrication: A gas sensor based on the ZnO / ZnWO4 composite material was fabricated by mixing ZnO / ZnWO4 material with deionized water and anhydrous ethanol to form a paste, which was then coated onto a ceramic tube (4 mm in length, 0.8 mm in inner diameter, and 1.2 mm in outer diameter). A Ni-Cr alloy wire was inserted into the ceramic tube, and the operating temperature of the sensor was controlled by adjusting the current flowing through the Ni-Cr alloy wire. Finally, the sensor was aged at 80°C for 2 days to enhance its response stability.

[0059] Experimental Example Gas sensors were prepared using the gas-sensitive materials from the examples and comparative examples, and their sensitivity and other properties were tested.

[0060] like Figure 1 As shown, Figure 1 (a) is a SEM image of the composite material after CVD calcination for 2 h; (b) 4 h, (c) 6 h, (d) 8 h, (e) are SEM images of WO3 material, (f) is a SEM image of pure ZnO material, and (g) is a SEM image of ZnO / ZnWO4 material synthesized by hydrothermal method.

[0061] As can be seen in Examples 1-4, as the CVD calcination time increases from 2h to 6h, the composite material gradually changes from a flower-like structure composed of sheets to a columnar agglomeration of sheets into a flower-like structure; when the calcination time increases to 8h, the columnar morphology gradually becomes less obvious, and the agglomerated flower-like structure becomes dispersed. The WO3 material in Comparative Example 1 exhibits a nanosphere morphology; the ZnO material prepared by CVD in Comparative Example 2 exhibits a columnar morphology; and the ZnO / ZnWO4 synthesized by hydrothermal method in Comparative Example 3 exhibits a rough rod-like morphology.

[0062] like Figure 2 As shown, X-ray powder (XRD) characterization of the products obtained in Examples 1-4 revealed diffraction peaks for both the corresponding wolframite-type ZnWO4 and the corresponding hexagonal wurtzite ZnO. The diffraction peaks of ZnO were consistent with the standard card (JCPDS No. 36-1451), indicating high crystallinity. The diffraction peaks of ZnWO4 were consistent with the standard card (JCPDS No. 15-0774) of the original ZnWO4, indicating that ZnWO4 formed a monoclinic phase.

[0063] like Figure 3 As shown, the sensors in Examples 1-4 were tested to assess their sensing characteristics for 30ppm H2S gas within a temperature range of 160℃-240℃. The test results showed that the gas sensors made of four sensitive materials, ZW1, ZW2, ZW3, and ZW4, exhibited the highest sensitivity for 30ppm H2S gas at 200℃, while the sensor in Comparative Example 1 showed the highest sensitivity at 160℃.

[0064] like Figure 4 As shown, the sensitivity of seven sensors to 50 ppm H2S and 2 ppm NO2 at the optimal temperature is compared. In Comparative Example 1, the WO3 sensor has a sensitivity of 67.9 to 50 ppm H2S at 160℃, the ZnO sensor in Comparative Example 2 has a sensitivity of 1.52 to 50 ppm H2S at 300℃, and the ZnO / ZnWO4 sensor in Comparative Example 3 has a sensitivity of 29.6 to 2 ppm NO2 at 110℃.

[0065] In Examples 1-4, the sensors of ZnO@ZnWO4 composite materials were tested at 200°C for 50ppm H2S. As the CVD calcination time increased, the sensor sensitivity showed a decreasing trend. In Example 1, the sensitivity was the highest when the CVD calcination time was 2h, with a response value of 386.5.

[0066] like Figure 5 The figure shows the sensitivity-concentration gradient characteristic curve of the sensor in Embodiment 1 of the present invention for H2S gas at the optimal operating temperature. The sensor in Embodiment 1, at an operating temperature of 200℃, can detect H2S concentration down to a lower limit of 0.05 ppm; the sensitivity for 2 ppm H2S is 49.6. The sensitivity-gas concentration function curve for 0.05-50 ppm H2S shows that the sensor's sensitivity increases with increasing H2S concentration.

[0067] like Figure 6 As shown in the figure, the response bar chart of the sensor based on ZW1 material in Example 1 to 30 ppm of different gases (H2S, NO2, NH3, CO2, Alcohol, Acetone) at the optimal operating temperature of 200℃ shows that the sensor's response sensitivity to 30 ppm H2S is much higher than that of the other interfering gases.

[0068] like Figure 7 As shown, the sensor prepared based on the ZW1 sample in Example 1 was subjected to a 30-day (1-month) stability test in an environment with a humidity of 25% RH. Under operating conditions at 200°C, although the sensitivity and baseline resistance fluctuated slightly during the test, they remained relatively stable overall, demonstrating that the sensor exhibits good long-term stability.

[0069] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of this application. It should be noted that, for those skilled in the art, several improvements and modifications can be made to this application without departing from the principles of this application, and these improvements and modifications also fall within the protection scope of the claims of this application.

Claims

1. A method for preparing a ZnO@ZnWO4 composite material, characterized in that, include: Mesoporous WO3 nanomaterials were prepared by solution evaporation-induced self-assembly. The WO3 nanomaterials were combined with zinc salts in situ by chemical vapor deposition to generate ZnO@ZnWO4 composite material. The ZnO@ZnWO4 composite material has a flower-like structure.

2. The preparation method according to claim 1, characterized in that, The deposition time for the chemical vapor deposition method is 2-8 hours.

3. The preparation method according to claim 2, characterized in that, The deposition time for the chemical vapor deposition method is 2 hours.

4. The preparation method according to claim 2, characterized in that, The zinc salt includes ZnCl2.

5. The preparation method according to claim 4, characterized in that, The mass ratio of WO3 nanomaterials to ZnCl2 is 1:3-1:8.

Citation Information

Patent Citations

  • Synthesis method of ball-flower shaped structure ZnO / ZnWO4 photocatalyst

    CN107224972A

  • Zinc tungstate / zinc oxide heterogeneous nanofiber as well as preparation method and application thereof

    CN113550025A